Pengaruh Motivasi Kerja Terhadap Kinerja Karyawan Pada PT. TASPEN (Persero) Cabang Manado - Orocomna, Cion; Tumbel, Tinneke M.; Asaloei, Sandra I. (Sam Ratulangi University, 2018)
This research was motivated by problems found in the office of PT. TASPEN (Persero) Manado Branch, which in employee performance lacks productive work motivation by using work time so that the amount of work that is not solved by what is done by each employee. And the obstacles faced are when employees cannot complete a job in carrying out their responsibilities as employees at PT. TAPSEN (Persero) Manado Branch. The arrangement of the arrangement is one aspect that must applied in the office to support the achievement of the goal of increasing productivity and performance of office employees.In this study, the method used was quantitative descriptive research method by distributing questionnaires to 50 respondents who were sample in this study. Data collected with a questionnaire that had been teste for validity and reliability.And our data analysis is descriptive and inferential statistics, which consist of simple correlation coefficients and regressions that are done using the SPSS for Windows version 24.0.The results showed that there was a significant influence between work motivations on employee performance. From this result is done and followed by data analysis obtained, then there is a significant influence between the influence of work motivation on employee performance at PT.TASPEN (Persero) Branch Manado and this means the working hypothesis or alternative hypothesis is accepted. This means that there is a positive influence between work motivation on employee performance and the level of influence of 21.3%. For this reason, recommended that more work motivation to increase in employee performance.Keywords: Work Â Motivation. Employee Performance